Word-Forming Affixes іn оfficial Letters оf Khan Abulkhair - Ү.Т., Қыдырбaевa; Э.А., Монтaнaй (Journal of Oriental Studies, 2019)
The article studied the linguistic structure of the written official letters to Russian empresses and ambassadors from Abulkhair Khan, who in the 18th century headed the power in the Kazakh steppe. The main goal of the research work is the definition of word-forming suffixes in official letters, received as a form of research work, by character and usage, research in comparison with historical Turkic languages and reflection of their continuity with modern Kazakh language. In the Kazakh steppe, handwritten materials of various content, written in the Chagatay language, are still relevant and important issues that require comprehensive study. Among them, the manuscripts of the Khanate era have a great influence on such sciences as history, philology and sociology. In the course of the study, the comparative-historical method was used and word-formation suffixes in the Old Turkic, Old Uigur, Karhan and Kipchak languages are considered. In addition, brief characteristics of the functionality were given with examples of the use of suffixes. The expected result of the research work is the definition of the use of word-forming suffixes in the historical Turkic language at the Khan stage and in the modern Kazakh language, as well as the prioritization of Chagatai and Kipchak language elements in letters. Key words: word-forming suffixes, Kazakh language, Turkic language, official letters.